Xenophobia and Discrimination - Ulloa Aiza, Sara (2002)
The problem of xenophobia or intolerance towards people of other nations, races, or ethnic groups other than one's own has been part of history since ancient civilizations and has often been latent in relationships and struggles for economic power.